Beyond IQ: The Rising Value of Extraversion - Izadi, Ramin; Tuhkuri, Joonas (Journal of Labor Economics, 2026)
We analyze trends in labor-market returns to psychological traits using data from half a million Finnish men from 2001 to 2015. Cognitive skills' value declined, while noncognitive skills' value increased. Our novel findings show that extraversion drives this rise, while conscientiousness remains stable. Extraversion's rising returns are most pronounced for lower earners and those on the employment margin. These traits predict different labor market paths: extraversion predicts lower education and more work experience, while cognitive ability and conscientiousness lead to higher education and high-paying jobs.